Purification and Characterization of an Active Principle, Lawsone, Responsible for the Plasmid Curing Activity of Plumbago zeylanica Root Extracts - Patwardhan, Rajashree Bhalchandra; Dhakephalkar, Prashant Kamalakar; Chopade, Balu Ananda; Dhavale, Dilip D.; Bhonde, Ramesh R. (Frontiers in Microbiology, 2018)
Abstract Plasmid curing is the process of obviating the plasmid encoded functions such as antibiotic resistance, virulence, degradation of aromatic compounds, etc. in bacteria. Several plasmid curing agents have been reported in literature, however, no plasmid curing agent can eliminate all plasmids from different hosts. Hence, there is always a need for novel plasmid curing agents that can be effectively used for reversal of plasmid encoded functions such as virulence, antibiotic resistance, etc. In the present study, an active principle responsible for the plasmid curing activity was purified from roots of Plumbago zeylanica by bioassay guided fractionation and identified as 2-hydroxy-1,4-naphthoquinone (lawsone), on the basis of spectral and analytical data such as NMR, GCMS, FTIR. Plasmid curing activity of lawsone was observed against reference as well as wild plasmids (pBR322, pRK2013, R136, pUPI281 and pUPI282) residing in a range of hosts. Curing of plasmid was confirmed by agarose gel electrophoresis. MICs of antibiotics against A. baumannii A24 (pUPI281) and E. coli (pRK2013) decreased significantly in presence of lawsone suggesting synergy between lawsone and antibiotics. Lawsone also inhibited transfer of plasmid pRK2013 to E. coli either by transformation or conjugation. Viability assays (MTT) revealed that lawsone was not toxic to mammalian cells. Thus, the present investigation has revealed lawsone as an effective plasmid curing agent capable of suppressing development and spread of antibiotic resistance. Further, lawsone has important application in basic research to identify phenotypes encoded by the plasmids in plasmid curing experiments. To the best of our knowledge this is the first report of plasmid curing activity of lawsone isolated from roots of P. zeylanica.